(untitled) (Bangladesh Journal of Botany, 2025)
To investigate the effects of different moisture on photosynthesis and biomass accumulation in kernel-apricot at seedling stage, the cultivar ‘Zhongren 7’ was used as the experimental material. Six water levels of T1 (15.0±0.5%), T2 (13.0±0.5%), T3 (11.0±0.5%), T4 (9.0±0.5%), T5 (7.0±0.5%) and T6 (5.0±0.5%) treatment were adopted. The results showed that the Pn, Tr, Ci and Gs gradually decreased with the water stress (WS), while the WUE reached the maximum at 8.0±0.5%. The diurnal variation curve of the Pn was unimodal indicated that there was no "noon break”. The LSP was gradually decreased, and the LCP was gradually increased, and the Fv/Fm, Fm, ETR and qP were gradually decreased with the WS, instead of the gradual increase of qN, the increase was reduced at the beginning at first and then gradual decrease of F0 was found. The height, diameter, root length etc., were decreased with the WS, while the root-top ratio was increased. Therefore, the suitable soil moisture was to 9.0%-15.0%, and the optimum was to13.0% while the limit was to 5.0%. Bangladesh J. Bot. 54(3): 499-508, 2025 (September)